2022
DOI: 10.3389/fonc.2022.872995
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome as a Risk Factor of Endometrial Cancer: A Nationwide Population-Based Cohort Study of 2.8 Million Women in South Korea

Abstract: BackgroundA positive relationship was reported between metabolic syndrome and the risk of endometrial cancer. Studies on the relationship between metabolic syndrome and endometrial cancer have been mainly conducted in post-menopausal women. We aimed to investigate the risk of endometrial cancer according to metabolic syndrome and menopausal status using the Korean nationwide population-based cohort.MethodsWe enrolled 2,824,107 adults (endometrial cancer group; N = 5,604 and control group; N= 2,818,503) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Of 127 meta-analyses that included cohort studies, body mass index (BMI), waist-to-hip ratio, and nulliparity were associated with increased endometrial cancer risk [20]. Additionally, a substantial population-based cohort study of Korean women reported metabolic syndrome as another risk factor [21]. The prevalence of metabolic syndrome increased among adolescents in Korea between 2007 and 2018, with changes in dietary habits and physical inactivity being the contributing factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…Of 127 meta-analyses that included cohort studies, body mass index (BMI), waist-to-hip ratio, and nulliparity were associated with increased endometrial cancer risk [20]. Additionally, a substantial population-based cohort study of Korean women reported metabolic syndrome as another risk factor [21]. The prevalence of metabolic syndrome increased among adolescents in Korea between 2007 and 2018, with changes in dietary habits and physical inactivity being the contributing factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of menopause on MetS goes beyond a simple pre-versus post-distribution [23,24]. Research from Korea, analyzing over 1,000 women, suggests a link between the elapsed time since menopause and the specific components of MetS a woman might experience.…”
Section: Time Since Menopause and Tailored Risk Assessmentmentioning
confidence: 99%